Business Cycle Asymmetries and the Labor Market - Christian Merkl; Britta Kohlbrecher (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
This paper shows that the matching function and the Beveridge curve in the United States exhibit strong nonlinearities over the business cycle. These patterns can be replicated by enhancing a search and matching model with idiosyncratic productivity shocks for new contacts. Large negative aggregate shocks move the hiring cutoff point into a part of the idiosyncratic density function with higher density and thereby generate large, asymmetric job-finding rate and unemployment reactions. Our proposed mechanism is of high relevance as it leads to time varying effects of certain policy interventions.
Keywords: E24; E32; E00; 330